BIM ADOPTION IN ARCHITECTURAL EDUCATION AND PROFESSIONAL PRACTICE: A SYSTEMATIC LITERATURE REVIEW - Andréen B.C.; Andersson L.M. (JoDA Journal of Digital Architecture, 2026)
The increasing integration of Building Information Modeling (BIM) has fundamentally reshaped architectural education and professional practice. However, disparities persist between academic instruction and real-world implementation, creating gaps in skills, workflows, and professional readiness. This study aims to systematically examine patterns, challenges, and opportunities associated with BIM adoption across architectural education and professional practice. A Systematic Literature Review was conducted using a structured PRISMA-based protocol, focusing on peer-reviewed journal articles published between 2013 and 2024. Database searches were performed in Scopus and Web of Science using predefined keywords related to BIM, education, and professional practice. Following strict inclusion and exclusion criteria, 68 articles were analyzed through thematic synthesis and comparative mapping. The results reveal that educational adoption primarily emphasizes technical proficiency, while professional practice prioritizes interdisciplinary collaboration and process integration. Key challenges include curriculum rigidity, limited industry-academia alignment, and uneven technological readiness. Conversely, opportunities emerge in collaborative learning models, competency-based curricula, and integrative digital workflows bridging education and practice.